2023
DOI: 10.1002/aenm.202300503
|View full text |Cite
|
Sign up to set email alerts
|

The Weyl Semimetals MIrTe4 (M = Nb, Ta) as Efficient Catalysts for Dye‐Sensitized Hydrogen Evolution

Abstract: The prevalent global energy crisis calls for searching viable pathways for generating green hydrogen as an alternative energy resource. Dye-sensitized photocatalytic water splitting is a feasible solution to produce green hydrogen. However, identifying suitable catalysts has been one of the bottlenecks in driving dye-sensitized photocatalysis efficiently. In this work, a new class of electrocatalysts is reported based on the layered Weyl semimetals MIrTe 4 (M = Nb, Ta) for the Eosin Y (EY)-sensitized hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Remarkably, the two above-mentioned properties have been experimentally confirmed. 11,26–28 In fact, recent research results have also confirmed the feasibility of topological materials, such as topological insulators Bi 2 Se 3 and Bi 2 Te 3 , 29,30 Weyl semimetal TaAs family, 8 TaTe 4 31 and NiSi, 32 multifold degenerate semimetals PtGa, PtAl, Nb 2 S 2 C and C12A7:4e − , 33–35 nodal line semimetal TiSi family 22 and semiconductor MoS 2 with floating surface states 36 in the field of catalysis.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Remarkably, the two above-mentioned properties have been experimentally confirmed. 11,26–28 In fact, recent research results have also confirmed the feasibility of topological materials, such as topological insulators Bi 2 Se 3 and Bi 2 Te 3 , 29,30 Weyl semimetal TaAs family, 8 TaTe 4 31 and NiSi, 32 multifold degenerate semimetals PtGa, PtAl, Nb 2 S 2 C and C12A7:4e − , 33–35 nodal line semimetal TiSi family 22 and semiconductor MoS 2 with floating surface states 36 in the field of catalysis.…”
Section: Introductionmentioning
confidence: 82%
“…At present, the study and calculations of topological catalysts using PBE-D2 have obtained good test results. 29–36 The HER of Mg 3 Bi 2 was performed in the supercell structure of dimension 2 × 2 × 4.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…The validity of this hypothesis has already been substantiated in various chemical processes, where topological materials have consistently demonstrated their capacity to enhance catalytic efficiency [21][22][23][24][25][26][27][28]. Importantly, the catalytic performance of these topological materials is intimately linked to their unique topological characteristics, particularly the dimension of their edge and surface states as highlighted in Meng et al's work in advanced science [26].…”
Section: Introductionmentioning
confidence: 90%
“…Based on the topological band theory, topological materials are characterized by symmetry-protected topological surface states (TSSs), which are immune to local perturbations without breaking the bulk topology. TSS-relevant quantum phenomena have been intensively studied by the physics community. Recently, with the application of topological materials in the field of chemistry, a new interdiscipline called topological catalysis has appeared. In heterogeneous catalysis, the reactant adsorption, electron transfer, and product desorption are highly sensitive to the surface environment, so a robust TSS offers an exciting opportunity to design high-performance catalysts. Currently, although a variety of topological semimetal enhanced catalytic reactions are reported in oxygen and hydrogen evolution reactions (OER and HER), direct experimental evidence to identify the intrinsic TSS effect in topological catalysis is still lacking.…”
Section: Introductionmentioning
confidence: 99%